2018
DOI: 10.1002/hec.3840
|View full text |Cite
|
Sign up to set email alerts
|

The impact of financial incentives on health and health care: Evidence from a large wellness program

Abstract: Workplace wellness programs have become increasingly common in the United States, although there is not yet consensus regarding the ability of such programs to improve employees' health and reduce health care costs. In this paper, we study a program offered by a large U.S. employer that provides substantial financial incentives directly tied to employees' health. The program has a high participation rate among eligible employees, around 80%, and we analyze the data on the first 4 years of the program, linked t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The BHW dataset did not include information on whether employees received incentives to participate in interventions, but incentives may influence participation. In the United States, financial incentives are associated with greater participation in health risk assessments and biometric screenings, 14,37,38 increased smoking cessation rates via increasing self-efficacy, 39,40 improved glycemic control in diabetic patients, 41,42 and increased exercise adherence 43 relative to interventions without financial incentives. However, financial incentives may widen disparities in care-seeking 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The BHW dataset did not include information on whether employees received incentives to participate in interventions, but incentives may influence participation. In the United States, financial incentives are associated with greater participation in health risk assessments and biometric screenings, 14,37,38 increased smoking cessation rates via increasing self-efficacy, 39,40 improved glycemic control in diabetic patients, 41,42 and increased exercise adherence 43 relative to interventions without financial incentives. However, financial incentives may widen disparities in care-seeking 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 33% of large employers use financial incentives to increase employee participation in wellness programs (30), and nearly 50% of surveyed medium to large employers reported that they plan to implement behavioral economic techniques to assist employees in improving health and to reduce health care costs (31). However, many companies use large monetary rewards (in excess of $300 per employee) (32) and require in‐person visits for their weight loss programs (33‐35). Given that the incentives paradigm described in the current analysis has been found to be more cost‐effective than IBWL alone (25), there is potential for workplaces to optimize their financial investment while broadening the reach of their wellness programs and improving the health of their youngest employees.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Crowley-Henry, Benson and Al Ariss (2019) emphasised that, in order to attract, develop and retain key employees in organisations, it is important to understand the nature and context of their careers. Thus, Williams, Chen-Bowers, Lankford and Wolff (2019) (Alexander & Fry, 2019;Coyle, Abel, Sedani, Holes, & Dinkel, 2019;Einav, Lee, & Levin, 2019;Hartley & Young, 2019;Ncube, 2018;Warehime et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The management of employee well-being is very important as it is inextricably linked to the extent to which talent is effectively managed. This ultimately contributes to the creation of psychologically healthy workplace, which focuses on improving employee involvement, health and safety, employee growth and development, work-life balance and employee recognition (Einav et al, 2019;Meyers et al, 2019;O'Connor & Crowley-Henry, 2019;Painter-Morland et al, 2019).…”
Section: Practical Implicationsmentioning
confidence: 99%